The Quality Test of Psychomotor Competency Assessment Instrument during Physics Praxis at Senior High Schools - Iqlides Ahmad Miyaqi; Winarti Winarti (Jurnal Pembelajaran Fisika, 2022)
Praxis is an effective method in science learning, especially physics where there is interaction between teachers and students, and is guided by the scientific method. Learning with praxis provides direct experience with the scientific method. This study aims to test and determine the quality of psychomotor assessment instruments for dynamic fluid practicum. The applied method was quantitative. The quality test used empirical and field tests with expert judgment, physics teachers (the practitioners), and learners. The researchers collected the data with test and non-test techniques. The data collection instruments were the product validation sheet, item assessment sheet, and user's response. The quantitative data analysis used descriptive statistics. The researchers used V-Aiken for product validation, Pearson Product Moment for test item quality, and Cronbach Alpha to determine the item reliability. The researchers analyzed the responses with percentage values. The results showed the instrument quality and question items get a high V-Aiken score and get a significance value that fulfills the minimum value limit for validity and the reliability aspect get the high category. Then, responses from users represent that the majority of users agree about using the instrument so that the assessment instrument tested has adequate, feasible and adaptive quality to use in the physics praxis of Senior High Schools.Keywords: Assessment instrument, Psychomotor Competency, Reliability, Physics praxisDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202209